Stable sulfur and oxygen isotopes as geochemical tracers of sulfate in karst waters - Sun, Jing; Kobayashi, Tatsuaki; Strosnider, William H.J.; Wu, Pan (Journal of hydrology (Amsterdam), 2017)
[Display omitted] •Elucidating δ34SSO4, δ18OSO4 and δ18OH2O dynamics can guide remediation strategies.•Isotopic compositions with and without acid mine drainage (AMD) were different.•The sulfate in AMD was predominantly influenced by aerobic pyrite oxidation.•The mean proportion of sulfate oxygen derived from water was 40% in AMD.•Analysis revealed reservoir sediment contamination as a remediation priority. Karst water resources, which are extremely sensitive to mining activities, are critical for the support of human societies and ecological systems in many regions worldwide. In order to determine the sources and fate of dissolved sulfate in low-pH karst waters, hydrochemical variations of karst waters with and without acid mine drainage (AMD) impacts were investigated along with stable isotope dynamics. As expected, hydrochemical characteristics and isotopic compositions of the AMD and AMD-downstream water (ADW) were dramatically different from that of the non-AMD-impacted water (NAW). The sources of sulfur isotopes in sulfate were predominantly pyrite oxidation for the AMD and ADW, and atmospheric deposition for the NAW. Based on the general isotope-balance model, the relative proportions of sulfate oxygen derived from water and air were calculated. The mean proportion of sulfate oxygen derived from water in ADW was roughly double that of AMD. This suggests that the sulfate associated with AMD is predominantly influenced by aerobic pyrite oxidation, while that of ADW is likely affected by the dissolution of pyrite under anaerobic conditions in reservoir sediment. This observation was coincident with the noted variations of hydrochemical characteristics and was supported by principal component analysis. These results provide a better understanding of how stable isotopes of sulfate and water can be used to track mining contamination in karst aquifers, which could benefit remediation planning for these distinctive systems.